Astrocyte and Oligodendrocyte Responses From the Subventricular Zone After Injury - David-Bercholz, Jennifer; Kuo, Chay T.; Deneen, Benjamin (Frontiers in Cellular Neuroscience, 2021)
Under normal conditions, neural stem cells (NSCs or B cells) in the adult subventricular zone (SVZ) give rise to amplifying neural progenitor cells (NPCs or C cells), which can produce neuroblasts (or A cells) that migrate to the olfactory bulb and differentiate into new neurons. However, following brain injury, these cells migrate towards the injury site where they differentiate into astrocytes and oligodendrocytes. In this review, we will focus on recent findings that chronicle how astrocytes and oligodendrocytes derived from SVZ-NSCs respond to different types of injury. We will also discuss molecular regulators of SVZ-NSC proliferation and their differentiation into astrocytes and oligodendrocytes. Overall, the goal of this review is to highlight how SVZ-NSCs respond to injury and to summarize the regulatory mechanisms that oversee these glial response. These molecular and cellular processes will provide critical insights needed to develop strategies to promote brain repair following injury using SVZ-NSCs.